Higher taxon surrogacy and the reassembly of a forest spider (Araneae) assemblage following prescribed burning - Majer, Jonathan; Brennan, Karl; Ashby, Lachlan (2006)
Taxonomic impediments require us to know if simpler approaches such as using higher taxa or habitat surrogates can help assess the needs of invertebrates when managing forests. This study tests whether higher taxon (families for species) and habitat (vegetation structure for species and families) surrogates might assist in determining the effects of prescribed burning on spiders. Spiders were sampled at sites representing a chronosequence of increasing ages since burning (0, 3, 6 and 9 years) by pitfall trapping and vacuuming from understorey vegetation in the South-west Botanical Province of Australia; a global biodiversity hotspot.